2013
DOI: 10.1017/jfm.2013.349
|View full text |Cite
|
Sign up to set email alerts
|

Split energy–helicity cascades in three-dimensional homogeneous and isotropic turbulence

Abstract: We investigate the transfer properties of energy and helicity fluctuations in fully developed homogeneous and isotropic turbulence by changing the nature of the nonlinear Navier-Stokes terms. We perform a surgery of all possible interactions, by keeping only those triads that have sign-definite helicity content. In order to do this, we apply an exact decomposition of the velocity field in a helical Fourier basis, as first proposed by Constantin & Majda (Commun. Math. Phys, vol. 115, 1988, p. 435) and exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(114 citation statements)
references
References 51 publications
6
106
2
Order By: Relevance
“…Such mechanism is consistent with the previous findings reported in [39,40], which showed that an inverse energy cascade develops also in homogeneous isotropic 3D turbulent flow when mirror symmetry is broken such that helicity has a well-defined sign at all wave numbers.…”
Section: Dimensional Transition and The Effect Of Rotationsupporting
confidence: 93%
“…Such mechanism is consistent with the previous findings reported in [39,40], which showed that an inverse energy cascade develops also in homogeneous isotropic 3D turbulent flow when mirror symmetry is broken such that helicity has a well-defined sign at all wave numbers.…”
Section: Dimensional Transition and The Effect Of Rotationsupporting
confidence: 93%
“…The present work is further timely since a number of works have been recently dedicated to the investigation of the dynamics of 3D turbulence in which only a part of the helical modes is retained [35,36], or in which the weight of the different helical contributions is artificially modified [39]. It was shown that in such a triadically modified flow, the energy cascades towards the large scales, and helicity towards the small ones.…”
Section: Discussionmentioning
confidence: 83%
“…However, helicity can always be finite locally, and an arbitrary velocity field can be written as the sum of helical modes [31], a decomposition used for instance to study the role of helicity using shell models [32][33][34]. Recent studies have considered Navier-Stokes turbulence where artificially only helical modes of a single polarity were retained [35,36]. In these flows, an inverse cascade occurs, even in the 3D isotropic case.…”
Section: Steady Helicity-free Flowmentioning
confidence: 99%
“…There is no doubt that triad truncation has intrinsic interest, just as do other truncations like standard Galerkin truncation, or truncations based on helical modes, as adopted by Cambon & Jacquin (1989), Waleffe (1992) and more recently Biferale, Musacchio & Toschi (2013). The special interest of triad truncation lies in the fact that evolution under this truncation can be explicitly calculated and compared with evolution under the Euler equations starting from the same initial conditions.…”
Section: Discussionmentioning
confidence: 99%